THE SOURCES OF ALISHER NAVOIY’S TREATISE ON ARUZ PROSODY - Yusupova Dilnavoz Rahmonovna (Modern American Journals, 2025)
This article provides the comparative analysis of theoretical sources that formed the foundations of Alisher Navoi's work “Mezon ul-Avzon”. This work of Alisher Navoi is devoted to the theory of aruz, which is the main poetic system of classical literature. In the introduction of his work the thinker and scholar had studied the Persian sources on aruz science created before himself, such as Nasriddin Tusi's “Me'yor ul-Ash'ar” and Abdurahman Jomi's “Risolai Aruz” where he said that he had read them before creating his own work. The author of the article considers it expedient to study "Mezon ul-avzon" in comparison with the sources created in the Persian language in order to show that Alisher Navoi had followed previous Persian scholars before he did his new creation (innovation) in the science of aruz. The article analyzes the main units of the literary arts in this direction: juzv, asl rukn, zihof, bahr and doira (circle).
Keywords: Aruz, juzv, rukn, sabab, vatad, fosila, meter, taqti, byte, misra (line)